Detrimental role for CCAAT/enhancer binding protein δ in blood-borne brain infection - JanWillem Duitman; Mercedes Valls Serón; JooYeon Engelen-Lee; Matthijs C. Brouwer; C. Arnold Spek; Diederik van de Beek (BMC Infectious Diseases, 2016)
Abstract Background The most frequent pathogen that causes bacterial meningitis is the Gram-positive bacterium Streptococcus (S.) pneumoniae. CCAAT/enhancer binding protein δ is a transcription factor that has recently been hypothesized to play a detrimental role in outcome of meningitis caused by S. pneumoniae. Here, we studied the role of C/EBPδ prior to the development of pneumococcal meningitis. Methods Wild-type and C/EBPδ-deficient mice (C/EBPδ−/−) were intraveneously infected with S. pneumoniae and sacrificed after 24 or 48 h. cebpδ expression, bacterial loads, inflammatory response and pathology in the brain were assessed. Results S. pneumoniae induces cebpδ expression in the brain during blood-borne brain infection. In comparison to wild-type mice, C/EBPδ−/− animals showed decreased bacterial loads in blood and brain 48 h after inoculation. In the blood compartment, the host inflammatory response was significantly lower upon infection in C/EBPδ−/− mice as compared to wild-type mice. Conclusion C/EBPδ facilitates bacterial dissemination to the brain and enhances the immune response in the blood compartment. Our study suggests that C/EBPδ plays a detrimental role during the initial development of blood-borne brain infection.